A novel integrated non-targeted metabolomic analysis reveals significant metabolite variations between different lettuce (Lactuca sativa. L) varieties. Issue 1 (25th June 2018) - Yang, Xiao; Wei, Shiwei; Liu, Bin; Guo, Doudou; Zheng, Bangxiao; Feng, Lei; Liu, Yumin; Tomás-Barberán, Francisco A; Luo, Lijun; Huang, Danfeng
Abstract: Lettuce is an important leafy vegetable that represents a significant dietary source of antioxidants and bioactive compounds. However, the levels of metabolites in different lettuce cultivars are poorly characterized. In this study, we used combined GC × GC-TOF/MS and UPLC-IMS-QTOF/MS to detect and relatively quantify metabolites in 30 lettuce cultivars representing large genetic diversity. Comparison with online databases, the published literature, standards as well using collision cross-section values enabled putative identification of 171 metabolites. Sixteen of these 171 metabolites (including phenolic acid derivatives, glycosylated flavonoids, and one iridoid) were present at significantly different levels in leaf and head type lettuces, which suggested the significant metabolomic variations between the leaf and head types of lettuce are related to secondary metabolism. A combination of the results and metabolic network analysis techniques suggested that leaf and head type lettuces contain not only different levels of metabolites but also have significant variations in the corresponding associated metabolic networks. The novel lettuce metabolite library and novel non-targeted metabolomics strategy devised in this study could be used to further characterize metabolic variations between lettuce cultivars or other plants. Moreover, the findings of this study provide important insight into metabolic adaptations due to natural and human selection, which could stimulate further research to potentially improve lettuce quality, yield, and nutritional value. Metabolic analysis: Not all lettuces are equal: Lettuces of different types show distinct variations in metabolic composition, which may have significance for their nutritional value. Lettuce ( Lactuca sativa ) has been cultivated for over 4000 years, resulting in a huge diversity of morphological types. Using a powerful combination of analysis techniques, an international team led by Francisco Tomas-Barberan at the Centre for Applied Soil Science and Biology of the Segura, Murcia, Spain, and Lijun Luo and Danfenge Huang of Shanghai Agribiological Gene Center, China, explored the chemical differences between thirty types of lettuce including leafy, butterhead, iceberg and romaine varieties. Their comprehensive 'metabolomic' approach identified significant differences in metabolism between leafy types and the three other, 'head' types, with the leafy varieties having higher concentrations of health-promoting compounds such as antioxidants. Their approach could in future be applied to other types of crops.